ANALISIS POLA KUNSUMSI MASYARAKAT NELAYAN DI DESA PAHLAWAN KECAMATAN TANJUNG TIRAM KABUPATEN BATU BARA - Bakhtiar Efendi (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2017)
The purpose of this study was to obtain empirical evidence that income, number of family members, and education affected by simultaneous consumption patterns of poor households in the district of Batu Bara. This study uses primary data. This study population is poor households in the district of Batu Bara. This sample selection method is by using Slovin. Data were analyzed use the regression analysis. The results indicate that income, family size, and education affect consumption patterns.